Entrepreneurship Education through Pesantren-Based Business Units: A Case Study of Female Vocational High School Students at Al-Faruqi Islamic Boarding School - Yazid Umar Nasution; Aidatul Husnah; Adinda Salsabilah Lubis (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study examined how entrepreneurship education was implemented through pesantren-based business units for female vocational high school students at Al-Faruqi Islamic Boarding School and explored the educational role attributed to these units by a key institutional stakeholder. An exploratory qualitative single-case study was conducted using a semi-structured interview with the coordinator of both the vocational school and pesantren business units. The transcript was examined through reflexive thematic analysis focusing on program planning, implementation, evaluation, and perceived student outcomes. The business units served dual institutional and educational functions by supporting pesantren operations while connecting the Fashion and Culinary Arts programs with production, business management, public marketing, and collaboration among students, teachers, and alumni. Program evaluation primarily involved resolving scheduling conflicts between entrepreneurial, academic, vocational, and religious activities. The informant associated student participation with vocational skill application, budgeting ability, opportunity recognition, independence, entrepreneurial aspirations, and selected alumni businesses. These outcomes represent stakeholder perceptions rather than independently verified effects. The study conceptualizes the pesantren-based business unit as a potential entrepreneurial learning ecosystem in which vocational learning, institutional enterprise, religious formation, and female students’ participation intersect. It also demonstrates that concrete business participation alone does not establish a complete experiential learning process without structured reflection, feedback, conceptualization, and assessment. The study extends entrepreneurship education research into a female vocational pesantren context and provides a framework for strengthening program design through explicit learning outcomes, progressive responsibilities, reflective activities, gender-responsive mentoring, competency-based assessment, systematic evaluation, multisource evidence, and longitudinal tracking.